Aplikasi Pemilihan Bibit Budidaya Ikan Air Tawar dengan Metode MOORA – Entropy - Muhammad Ashari, Arini, Fitri Mintarsih (Program Studi Sistem Informasi, 2017)
At the beginning of the start of the business of breeding fish selection of freshwater fish cultivation becomes a difficult thing to do. The results of interviews with the Center for Research and Development of Freshwater Aquaculture said that there are 8 factors that influence the selection of freshwater fish cultivation seeds, namely temperature, water pH, location, elevation, dissolved oxygen, pond area, the ideal length of enlargement, feeding easier, fish. This research uses Decision Support System with Multi Objective Optimization By Ratio Analysis (MOORA) method as ranking and Entropy as weighting. The incorporation of the MOORA and Entropy methods gives the recommendation result by combining the objective system's subjective and subjective weights. It used priority criteria with temperature value 0,222, water pH 0,194, Eatability 0,111, community interest toward fish 0,055, dissolved oxygen 0,138, land height 0,167, ideal length of fish enlargement 0,027, and pool area 0,083 produce catfish as the best alternative of fish breeder water with value -0.1009.Keywords: Information, fish, DSS, MOORA, Entropy